El hombre del rey : Robin Hood III - Donald, Angus, 1965- (Narrativas históricas Edhasa., 2012)
Entreated by a betrayed and imprisoned Richard the Lionheart to save England, Robin Hood, a renegade earl and former outlaw, embarks on a deadly mission at the side of loyal lieutenant Alan Dale in a heroic bid to restore the king to the throne.